Motion modeling from 4D MR images of liver simulating phantom - Kavaluus, Henna; Koivula, Lauri; Salli, Eero; Seppälä, Tiina; Saarilahti, Kauko; Tenhunen, Mikko (Journal of applied clinical medical physics, 2022)
Background and purpose A novel method of retrospective liver modeling was developed based on four‐dimensional magnetic resonance (4D‐MR) images. The 4D‐MR images will be utilized in generation of the subject‐specific deformable liver model to be used in radiotherapy planning (RTP). The purpose of this study was to test and validate the developed 4D‐magnetic resonance imaging (MRI) method with extensive phantom tests. We also aimed to build a motion model with image registration methods from liver simulating phantom images. Materials and methods A deformable phantom was constructed by combining deformable tissue‐equivalent material and a programmable 4D CIRS‐platform. The phantom was imaged in 1.5 T MRI scanner with T2‐weighted 4D SSFSE and T1‐weighted Ax dual‐echo Dixon SPGR sequences, and in computed tomography (CT). In addition, geometric distortion of the 4D sequence was measured with a GRADE phantom. The motion model was developed; the phases of the 4D‐MRI were used as surrogate data, and displacement vector fields (DVF's) were used as a motion measurement. The motion model and the developed 4D‐MRI method were evaluated and validated with extensive tests. Result The 4D‐MRI method enabled an accuracy of 2 mm using our deformable phantom compared to the 4D‐CT. Results showed a mean accuracy of <2 mm between coordinates and DVF's measured from the 4D images. Three‐dimensional geometric accuracy results with the GRADE phantom were: 0.9‐mm mean and 2.5 mm maximum distortion within a 100 mm distance, and 2.2 mm mean, 5.2 mm maximum distortion within a 150 mm distance from the isocenter. Conclusions The 4D‐MRI method was validated with phantom tests as a necessary step before patient studies. The subject‐specific motion model was generated and will be utilized in the generation of the deformable liver model of patients to be used in RTP.